IMPLEMENTASI WORK FROM HOME: KAJIAN TENTANG DAMPAK POSITIF, DAMPAK NEGATIF DAN PRODUKTIVITAS PEGAWAI - Bueti, Ahmad (STAI Darul Qalam Tangerang, 2022)
The Covid-19 pandemic has brought significant changes in various aspects of life, including the work system structure. The work system alteration as one of the government’s policies in the attempt to prevent Covid-19 is working from home or also known as WFH. This policy, which was implemented suddenly, presented challenges for civil servants in its implementation. This new work culture is certain to have positive and negative impacts both on institutions and for employees which in turn has an impact on productivity. By looking at the positive, negative and productivity impacts, it will provide an idea of ​whether or not the work from home system should be continued after the pandemic is over. This paper is limited to a literature review that requires follow-up research to obtain data that can be used as a basis for formulating recommendations for civil servants work system policies in the future